The impact of partial blood replacement on postoperative outcome for pediatric patients with cyanotic heart disease - Saleh, Mohammad (Journal of Cardiovascular Medicine and Cardiology, 2020)
Background: Pediatric patients with cyanotic congenital heart disease who underwent open heart corrective surgery, were unfortianetly suffering from postoperative clinical deterioration which may leads to morbidity and mortality. Most of blood transfusion indications are now well managed exclusively with blood component therapy, however concerns about logistics, safety, and relative efficacy making the blood transfusion a debating procedure in many cardiac centers around the world. The research aimed to investigate the partial blood replacement process for cyanotic pediatric patients by healthy RBCs (red blood cells), solving their postoperative clinical deterioration and proving that the RBCs membrane biomechanical characteristics alterations is the main cause of the adverse effects of prolonged hypoxia on the normal physiological functions of RBCs in oxygen transport and body tissue’s perfusion. Methods: 450 Pediatric patients with congenital heart disease were divided into three equal groups, group I acyanotic pediatric patients, group II cyanotic pediatric patients and group III cyanotic pediatric patients treated with the partial blood replacement process. Blood components biophysical characteristics and cardiovascular performance were investigated and the postoperative clinical course was estimated. Results: The results showed the improvement of group III pediatrics, as there were insignificant decrease in blood components characteristics, cardiovascular performance and postoperative clinical course estimation compared to group I. Conclusion: The partial blood replacement process after cardiopulmonary bypass procedure for pediatric patients with cyanotic congenital heart disease who undergo corrective congenital surgery, may help in improving their postoperative clinical course and outcomes.